Churchill's children : the evacuee experience in wartime Britain - Welshman, John (Oxford Univ. Press, 2010)
Introduction : a child's war -- Evacuation : just another word -- Operation Pied Piper -- The railway children -- Living out of a suitcase -- The official response -- A winter on welfare -- City and countryside -- Spitfire summer -- Victims or vandals? -- One year on -- The long haul -- Reconstruction -- Going home -- Ordinary people in extraordinary circumstances